Polycystic Kidney Disease in Rough Toothed Dolphins (Steno bredanensis) founded in the Paraná coast, Southern Brazil - Giglio Pires, Bárbara; Farias da Nóbrega, Daniela; Domit, Camila; Frederico Rodrigues Loureiro Bracarense, Ana Paula (Acta Scientiae Veterinariae, 2021)
Background: Renal cystic diseases (RCD) are characterized by cystic structures on renal parenchyma associated with obstructive lesions, membranous disruptions, and/or growth disturbances. The polycystic kidney disease (PKD) shows specific pathological characteristics, related to mutations on PKD1 and/or PKD2 chromosome locus on humans. In Persian cats and bull terriers the condition is like the human “adult-onset” PKD, while in Perendale sheep the “childhood”-like is described. In cetaceans, RCD are reported, however the characterization of PKD is scarcely described. This report aims to describe two cases of PKD and one of RCD in stranded Steno bredanensis, and to discuss the disease associated factors. Cases: Four rough-toothed-dolphins were found stranded in the Paraná coast, southern Brazil between 2016 to 2018, through the Santos Basin Beach Monitoring Project (PMP-BS), one of the systematic monitoring programs required by Brazilian Institute of Environment and Renewable Natural Resources (IBAMA) for the environmental licensing process of oil production and transport by Petrobras in the presalt province. In three animals histological sampling was performed. One of them (animal 3) was founded alive, presenting altered buoyancy with lateralization to the right and signs of pneumonia. The blood analysis showed anemia and leukocytosis. The animal showed poor clinical prognosis, and even with supportive treatment, come to death four days after the rescue. Routine autopsies were performed on all animals. Animals 1 and 2 presented macroscopically enlarged kidneys containing disseminated cystic structures in the parenchyma. On microscopic examination, the cortical region showed diffuse cystic structures delimited by variable thickness of fibrous tissue, usually compressing adjacent glomeruli, without concomitant inflammatory process. In these cases, the death was associated with the end stage renal disease. Animal 3 showed grossly few cystic structures, well delimited and replacing some reniculi. Tracheitis, granulomatous pneumonia, esophagitis, gastritis, enteritis and papilloma on penis and palate were observed. Microscopically, the cysts were lined by a single layer of columnar to cuboidal epithelial cells surrounded by extensive fibrotic tissue. Multifocal tubular necrosis was also noticed. Multifocal moderate nonsuppurative encephalitis with parasitic eggs and bacterial granulomatous hemorrhagic pneumonia were observed. In this case, the death was associated with the lesions in the nervous system. Discussion: Data concerning polycystic kidney disease on cetaceans and wild animals is limited, and no primary genetic pathway was associated. In the present study, the gross and histological aspects observed on two animals (1 and 2) are similar to the characteristics found in the human adult form of PKD, while the characteristics observed on animal 3 are consistent with usual cystic disease. In addition, the animals are aged like humans where the end stage renal disease occurs in patients around 70 years old. The kidney histological aspects observed in all animals are similar, however, animal 3 showed no renomegaly, a characteristic of PKD. Considering the genetic pathway involved in humans and some animal’s breeds, investigation on gene mutations in S. bredanensis could help to define if this is also a genetic disorder and increase the knowledge about PKD. Keywords: kidney, delphinidae, PKD, diagnostic pathology, cystic disease, rough toothed dolphin.